2020
DOI: 10.1016/j.ymthe.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Screening Strategy for Engineering Chimeric Antigen Receptors with Reduced On-Target, Off-Tumor Activation

Abstract: In recent years, chimeric antigen receptor (CAR) T cell cancer immunotherapies have advanced substantially in the clinic. However, challenges related to safety persist; one major concern occurs when CARs trigger a response to antigen present on healthy cells (on-target, off-tumor response). A strategy to ameliorate this relies on the complex relationship between receptor affinity and signaling, such that one can engineer a CAR that is only activated by tumor cells expressing high antigen levels. Here, we devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…While domain shuffling constitutes a powerful method for rapidly engineering new diversity in a protein, this can make the choice of screening strategy a challenging ordeal. Previous work for CAR engineering has relied on functional screening based on the expression of single reporter genes or proteins (e.g., IL-2, NFAT, CD69) in immortalized cell lines [15,[28][29][30]. While these approaches enable high-throughput screening of CAR libraries, they are limited by their uni-dimensionality: they generally reveal only a single aspect of the effector response and do not capture the full complexity of the deeply interconnected signaling network of T cell activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While domain shuffling constitutes a powerful method for rapidly engineering new diversity in a protein, this can make the choice of screening strategy a challenging ordeal. Previous work for CAR engineering has relied on functional screening based on the expression of single reporter genes or proteins (e.g., IL-2, NFAT, CD69) in immortalized cell lines [15,[28][29][30]. While these approaches enable high-throughput screening of CAR libraries, they are limited by their uni-dimensionality: they generally reveal only a single aspect of the effector response and do not capture the full complexity of the deeply interconnected signaling network of T cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted our previous CRISPR/Cas9 genome editing protocol [28] to introduce CAR genes at the TRAC genomic locus. Briefly, the ribonucleoprotein (RNP) particles were assembled by first duplexing the CRISPR RNA (crRNA) and trans-activating CRISPR RNA (tracrRNA) (IDT) through co-incubation at 95 o C for 5 minutes and cooling to room temperature.…”
Section: Primary Human T Cell Genome Editingmentioning
confidence: 99%
“…Single-chain variable fragments are still widely seen as the exogenous antigen-sensing domain in chimeric antigen receptors. They're made up of a flexible binder that joins a monoclonal antibody's variable heavy and light chains [5].…”
Section: Development In Chimeric Antigen Receptor Designsmentioning
confidence: 99%
“…Although subsequent tuning of any resulting CAR response can be achieved by empirical evaluation of various spacer and intracellular domains, an over-reliance on the availability of ‘off-the-shelf’ high(er) affinity scFvs may considerably restrict the potential for clinical CAR development and optimization. More recent insights have confirmed that CAR potency and in vivo performance is not strongly correlated with scFv (or ligand) affinity, with low to modest affinity clone variants showing superior performance over high affinity parents in terms of expansion and persistence, and in alleviating on-target/off-tumor toxicities 17 , 23 25 . Collectively, these observations suggest that many context-sensitive CAR-active clones of interest may fall below the screening thresholds applied during classical in vivo and in vitro antibody discovery cascades, or fail to perform adequately as surface receptors in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%